Insight into copper-cerium catalysts with different Cu valence states for CO-SCR and in-situ DRIFTS study on reaction mechanism. (1st May 2023) - Li, Jinfeng; Zhu, Jiexuan; Fu, Shiying; Tao, Lin; Chu, Bingxian; Qin, Qiuju; Wang, Jingkai; Li, Bin; Dong, Lihui
Graphical abstract: Highlights: CeO2 and CuO-CeO2 supports promote the design of Cu + -Ce and Cu 2+ -Ce system. The abundant Cu + in Cu + -Ce system promotes the adsorption of CO and the synergy between Cu + and Ce 4+ . The in-situ DRIFTS results in different NO + CO atmospheres explain oxygen vacancy is the site for decomposing NO. Two kinds of mechanism models for Cu + -Ce and Cu 2+ -Ce systems were proposed. Abstract: Copper-cerium catalysts have received extensive attention for their excellent catalytic performance in the field of NO reduction with CO. In this work, Cu + -Ce and Cu 2+ -Ce systems were designed to examine the catalytic potential of Cu + and Cu 2+ . A series of catalysts were characterized by XRD, BET, HRTEM, EDS, H2 -TPR, Raman, XPS and in-situ DRIFTS in different NO + CO atmospheres. Cu + -Ce catalyst possesses a large amount of Cu + that can promote the synergy between Cu + and Ce 4+ and adsorb CO to form Cu + -CO species consuming more active oxygen, thus generating more oxygen vacancies than Cu 2+ -Ce, which improve the catalytic performance of Cu + -Ce catalyst at low temperatures. In different NO + CO atmospheres, Cu + -Ce catalyst always maintains better catalytic performance to make an excellent universal applicability. In-situ DRIFTS in different NO + CO atmospheres provided evidence to confirm that oxygen vacancy is indeed active site for decomposing NO. And it also demonstrated that the CuCe/CuCe-S (Cu 2+ -Ce system) and CuCe/Ce-S (Cu + -Ce system) catalysts are dominated by L-H mechanism with different CO adsorption behavior at low temperatures.